“You never know what’s in front of you”: A mixed methods study of barriers and facilitators to physical activity among blind and low-vision adults with type 2 diabetes - Emily J. Nicklett; Meredith L. Stensland; Weidi Qin; Tiffany Walker; Turnip Van Dyke; Deven Murray; Beatriz Morales-Hernandez; Giselle Reinhardt Gillis; Julia J. Crowley (PLoS ONE, 2026)
Individuals living with type 2 diabetes and vision loss experience unique, under-researched barriers to physical activity, despite the important role exercise plays in diabetes management. This study examined physical activity participation among blind and low-vision adults with type 2 diabetes ( n = 30). Participants, ages 44–83, resided in Bexar County, Texas. Closed-ended surveys (conducted in English or Spanish) were administered to participants, followed by in-depth, semi-structured interviews. Interviews were audio-recorded, transcribed verbatim, and double-coded. Participants’ physical activity levels were determined using the Exercise Behaviors Scale. Data were analyzed using a convergent inductive-deductive design. Consistent with the Social-Ecological Model, five main themes and 11 subthemes emerged, depicting how individual/intrapersonal, interpersonal, institutional/organizational, community, and policy-level factors influenced participants’ physical activity participation. These factors can be specifically targeted both at local and broader levels to promote physical activity among individuals with concurrent type 2 diabetes and blindness/vision loss.